2014
DOI: 10.1007/s00221-014-4110-y
|View full text |Cite
|
Sign up to set email alerts
|

Temporal estimation with two moving objects: overt and covert pursuit

Abstract: The current study examined temporal estimation in a prediction motion task where participants were cued to overtly pursue one of two moving objects, which could either arrive first (i.e., shortest TTC) or second (i.e., longest TTC) after a period of occlusion. Participants were instructed to estimate TTC of the first-arriving object only, thus making it necessary to overtly pursue the cued object while at the same time covertly pursuing the other (non-cued) object. A control (baseline) condition was also inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Several PM experiments have documented dual-task interference costs (Baurès, Bennett, & Causer, 2015;Baurès, DeLucia, Olson, & Oberfeld, 2017;Baurès et al, 2010Baurès et al, , 2011DeLucia & Novak, 1997;Lyon & Waag, 1995;Oberfeld & Hecht, 2008). These experiments illustrate the difference between pre and post occlusion explanations.…”
Section: Alternative Explanations For Pm Effectsmentioning
confidence: 74%
“…Several PM experiments have documented dual-task interference costs (Baurès, Bennett, & Causer, 2015;Baurès, DeLucia, Olson, & Oberfeld, 2017;Baurès et al, 2010Baurès et al, , 2011DeLucia & Novak, 1997;Lyon & Waag, 1995;Oberfeld & Hecht, 2008). These experiments illustrate the difference between pre and post occlusion explanations.…”
Section: Alternative Explanations For Pm Effectsmentioning
confidence: 74%
“…To understand what could be the implication of this region in the TTC estimation, it is important to describe the different steps of the task. In the prediction motion paradigm we used, the task requires overt attention to the ball (Baurès et al, 2015), pursuit eye movements (Bennett et al., 2010), a dynamical representation of the ball's position (according to the cognitive motion extrapolation strategy) or TTC (according to the clocking strategy) during the occlusion time (Bosco et al., 2015; Makin, 2018) and a motor response to indicate the estimated arrival time. All these processes are known to involve the parietal area (e.g., Astafiev et al., 2003; Bisley et al., 2011; Harrison et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment 1, the two objects moved on parallel trajectories, separated by a small vertical distance that putatively permitted efficient perception of the TTCs of both objects. Indeed, it has recently been shown that observers can efficiently fixate on one object while accessing another object's TTC if the two objects are temporally or spatially close (Baurès, Bennett, & Causer, 2015). In Experiment 2, the two objects were distant from each other, likely making it much more difficult for participants to share visual attention between the two objects while maintaining their gaze on one of the objects.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%